CASP-12 as a measure of quality of life at older ages: comparing near and older elderly - Benítez-Llamazares, Nuria; Ferreira, Lara. N (My University, 2019)
It is well known that European governments face to an ageing society as result of the increasing life expectancy and the decreasing birth rates in recent decades. A growing part of the European population is living their “Third age”, and this new paradigm has become increasingly important and has become a major concern in public policy. It stands to reason that better conditions at these ages (health, economic status, happiness, family, etc.) surely influence this approach. The aim of this paper is to determinate the key factors that affect the Quality of Life (QoL) of the elderly in the European countries. Additionally, we try to identify if significant differences are resulted in QoL of the elderly in regions across Europe (southern, northern and eastern). We have used data from the most recent wave released in SHARE (Survey of Health, Ageing and Retirement in Europe, wave 7) for all European countries participants in the survey. Then, we used the SHARE version of the CASP-12 scale to determinate if there are significant discrepancies between European countries. Despcritive results shown significant differences raised in QoL of the elderly by regions across Europe (northern and eastern) if life satisfaction is self-reported. However, using CASP-12 as key indicator of quality of life and life satisfaction the results are more heterogenous.
Keywords: Ancianos - Protección, asistencia, etc. - Paises de la Union Europea; Calidad de vida - Paises de la Union Europea; Quality of life; SHARE; CASP-12; Elderly; Measurement